2007
DOI: 10.1093/jhered/esm051
|View full text |Cite
|
Sign up to set email alerts
|

DLA-DRB1, DQA1, and DQB1 Alleles and Haplotypes in North American Gray Wolves

Abstract: The canine major histocompatibility complex contains highly polymorphic genes, many of which are critical in regulating immune response. Since domestic dogs evolved from Gray Wolves (Canis lupus), common DLA class II alleles should exist. Sequencing was used to characterize 175 Gray Wolves for DLA class II alleles, and data from 1856 dogs, covering 85 different breeds of mostly European origin, were available for comparison. Within wolves, 28 new alleles were identified, all occurring in at least 2 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
0
25
1
Order By: Relevance
“…The polymorphism of the dog leukocyte antigen (DLA)-DRB1 was analyzed 17,18. DLA-DRB1 was chosen because it represents the most highly polymorphic class II locus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymorphism of the dog leukocyte antigen (DLA)-DRB1 was analyzed 17,18. DLA-DRB1 was chosen because it represents the most highly polymorphic class II locus.…”
Section: Resultsmentioning
confidence: 99%
“…This is not surprising in view of the high degree of polymorphism of DRB1 17,18. The possibility of a PCR error was excluded by employing a proof-reading polymerase in the first and second PCR rounds.…”
Section: Resultsmentioning
confidence: 99%
“…Banks and Victoria Island shared one allele found in no other population (total frequency 1%, data not shown), but private alleles were not observed within any island sample. Major Histocompatibility Complex genes from Alaskan and Canadian wolves showed: greatest diversity with unique haplotypes in boreal forest populations; moderate diversity with no unique haplotypes in mainland barren-ground populations; and lowest diversity in Banks Island wolves (Kennedy et al 2007). Our own preliminary mtDNA sequencing revealed lower haplotype diversity in, and no haplotypes unique to the Arctic Islands (unpublished data).…”
Section: Glacial Refugia In the Canadian Arctic Archipelagomentioning
confidence: 95%
“…To identify the alleles from heterozygous individuals, all heterozygotes were cloned using GeneJET PCR Cloning Kit (Fermentas, Burlington, Canada). All novel alleles were verified by a second independent analysis using another set of PCR primers (Kennedy et al, 2007a), to ensure that these alleles had not gone undetected in earlier studies because of primer mismatch (see Supplementary methods for detailed methodology).…”
Section: Dna Techniquesmentioning
confidence: 99%
“…The sequences included dogs mainly from Europe (Sarmiento and Storb, 1990;Murgia et al, 2006;Kennedy et al, 2007b), but also a lesser number of dogs from other regions (Runstadler et al, 2006) and wolves (Seddon and Ellegren, 2002;Kennedy et al, 2007a). To study phylogenetic relationships between the newly identified and previously published DLA alleles, a neighbor-joining tree was constructed for dog and wolf alleles with the software MEGA 4.1 (Tamura et al, 2007) using JukesCantor distances.…”
Section: Analyses Of Sequence Data and Tree Constructionmentioning
confidence: 99%